Comparison of Operative Outcomes of Open Thyroidectomy with Electrothermal Bipolar Vessel Sealer versus Conventional Hemostasis for Benign Thyroid Swelling in Adults Population: Thyroidectomy with Electrothermal Bipolar Vessel Sealer versus Conventional Hemostasis - Islam, Muzammal; Nazir, Absar; Usman, Muhammad Tahir; Jamil, Tayyaba; Bano, Ghazala; Raheem, Mehwish; Jan, Mohammad Amir; Afzal, Saiqa; Zahra, Syeda Aleena (Pakistan Journal of Health Sciences, 2025)
Precise dissection and effective hemostasis are crucial for safe thyroid surgery. The bipolar vessel sealer, a first-generation electrosurgical instrument, is widely used in thyroidectomies to improve hemostasis, reduce tissue trauma, shorten surgery time, and eliminate the need for sutures. Objective: To compare the operative outcomes of electrothermal bipolar vessel sealer in total thyroidectomy. Methods: At the Department of Surgery, Sir Ganga Ram Hospital, from August 2024 to January 2025, a quasi-experimental study was carried out, involving 80 patients undergoing total thyroidectomy. Exclusion criteria included patients with significant comorbidities, bleeding disorders, or renal and liver dysfunctions. The study participants were divided into two groups: Group A (bipolar vessel sealer) and Group B (clamp-and-tie technique). Primary outcomes included surgery duration, intraoperative blood loss, and hospital stay. Data were entered and analyzed by SPSS version 25.0. Results: The average age of patients was 35.5 ± 4.9 years. Group A had 70% female and 30% male, while Group B had 77.5% female and 22.5% male. Group A had significantly shorter hospital stays (3.8 ± 1.2 days) compared to Group B (5.2 ± 2.3 days, p=0.000). Intraoperative blood loss was significantly lower in Group A (109.7 ± 7.3 mL) compared to Group B (154.3 ± 6.7 mL, p<0.000). Surgery duration was longer in Group A (121.3 ± 13.1 minutes) than in Group B (94.3 ± 11.3 minutes, p<0.05). Conclusions: It was concluded that the bipolar vessel sealer in total thyroidectomy for benign thyroid swelling is effective, and results in shorter hospital stays without increasing complications or costs.